ANALISIS PENCAPAIAN IMUNISASI DASAR LENGKAP DI PUSKESMAS - Qamarya, Nurul; Zamli, Zamli; Hafsah, Hafsah; Nopianto, Nopianto; Rahmah, Lestari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Puskesmas Bangkinang Kota is one of the Puskesmas with the lowest achievement of basic immunization in Kampar Regency in 2022. The purpose of this study was to analyze the implementation of the basic immunization program at the Bangkinang Kota Health Center in 2022. The study used an analytical qualitative method conducted at the Bangkinang City Health Center in July 2023. The research informants consisted of main informants and supporting informants. The research instrument used interview guidelines and observation sheets. Data analysis was done by data triangulation. The results showed that the implementation of immunization activities at the Bangkinang City Health Center had been carried out. However, in its implementation there are several obstacles such as limited human resources due to the absence of a special team involving cross-programs within the puskesmas, while immunization officers are also involved in other puskesmas programs. So it is suggested that the Bangkinang Kota Health Center can maximize the role of cadres in supporting the implementation of immunization by conducting coordination meetings and providing rewards for cadres with good performance.Keywords: Immunization, Puskesmas, Human Resources, Budget